Sintomas de estres hidrico y DE "SECA" EN ENCINAS (Quercus ilex subsp. ballota) INOCULADAS CON Phytophthora cinnamomi EN UNA DEHESA DEL CENTRO DE ESPAÑA - TUSET, JUAN J; HINAREJOS, C; MIRA, J L; COBOS, J M (II Congreso Forestal Español, 1997)
Phytophthora cinnamomi is a causal agent for the "seca" (oak decline) of the Mediterranean Quercus. The disease symptoms consist basically of a decay of the trees canopy that may occur as a slow decline: gradualleaves fall and presence of partially or totally defoliated branches, or as a quick decline: rapid decline of branches, leaves remaining attached sorne time, and dead trees. There may also be blackish gummose exudates on trunk and main branches. The "seca" reached epidemic rates in the various evergreen oaks or cork oaks distributed on Andalusia, Castilla-La Mancha and Extremadura since 1990-91. From then in the soils of these forestry areas and on feeder roots of cork oaks and evergreen oaks, P. cinnamomi were isolated along the climatological seasons until now. The continued presence of the fungi has lead to determine the susceptibility of Q. ilex subsp. hallota on adult trees in the field. Adult evergreen oak plants were inoculated with young mycelium of P. cinnamomi at La Iglesuela (Toledo) in spring, 1994. At two years, the development of this fungus on roots, trunks and branches of evergreen oak:, shows a great pathogenic capacity and it has achieved the reproduction of clear symptoms of "seca"
Keywords: canker; oak: decline; Pathogenicity; phytophthora cinnamomi; Quercus ¡lex subsp. ballota